STATE DILEMMAS IN THE CONTEMPORARY WORLD ORDER - I. N. Timofeev (Vestnik MGIMO-Universiteta)
The problems of the world order is often seen through the interaction of the leading centers of power. Nevertheless there is another approach, locating actorhood in the state, which forms the world order. State acts in international affairs, it has the right of legitimate violence, it also has the ability to concentrate the economic and human resources. Obviously, the nature of the state as part of the international system has an effect on the system itself, defining its key parameters. From that point of view, some questions arise: what happens to the state? What is the effect of its transformation on the contemporary world order? Why the state is changing? What hierarchy of states exists in the contemporary world order? The author proceed from the following theses. First, the nation state is no longer a universal formula of nation building. However, there is no balance between two key foundations of a legitimate order - fairness and efficiency. Second, the current world order is a mosaic of fundamentally different states. Each state is trying to find a formula for the combination of a fairness and efficiency. These formulas do not always coincide with each other, and it underlays the stability in international relations. Third, a small group of major powers still play the key role in the world order. The issue of sovereignty of many countries remains open. World order, as well as a state, is characterized by imbalance between equity and efficiency. The awaited harmony of these two principles may be spoofed again the triumph of efficiency oover justice -maintenance of order through the balance of power and a rigid hierarchy.